Orthopedic Rehabilitation, Assessment, and Enablement - Ip, David. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Medical practitioners involved in the treatment of diseases, disorders, and injuries of the musculoskeletal system will appreciate the very - portant role of rehabilitation. Following the publication of two books Orthopedic Principles – A Resident’s Guide and Orthopedic Traumatology – A Resident’s Guide, Dr. Ip has expended further time and effort to p- duce a third book, which contains a comprehensive account of orthop- dic rehabilitation. The material is easy to grasp with succinct points. There are 19 chapters, arranged in a logical sequence. The first ch- ter gives a holistic view of what the rehabilitation process should include and emphasises that the unique feature of a rehabilitation service is thinking about a patient and his problems, not simply doing something to the patient, and the focus should be on trying to help each patient achieve his own goals. Chapters 2 to 8 are about the rehabilitation tools for assessing, inv- tigating and treating patients. Chapters 9 to 17 are about rehabilitation for specific types of musculoskeletal disorders, each of which has its own complex problems, requiring practitioners to gain further in-depth training and experience to give effective treatment. The format is similar to the previous two books, containing brief, yet comprehensive, core information on the subject, which can be enhanced by more detailed literature review if necessary. This unique feature r- ders the book very readable.